Meditations on exile in the text 'I do as the swimmer does in the sea' by Sadek Aïssat and its relation with the poem 'El Meknassia' - Souilah, Samira (Anaquel de Estudios Árabes, 2021)
Exile, in the text of Sadek Aïssat, is a configuration of the reality of being through the immigrant character mirror image of the oppressed, the uprooted living an eternal quest for the self. The writer does not focus, by dealing with exile, on reminiscences, on childhood, mother, the institutions building the identity and otherness themes. However, he traces an inner path that paints his spatio-temporal uprooting, where the writer searches himself. This discomfort is detected through the misguidance of the character who has neither landmarks, nor identity denying his life to the point of tearing his passport. The aim of this article is, first, to show the construction of exile in the text I do as the swimmer does in the sea by Sadek Aïssat, then, put it connected with the poem El Meknassia which deals with the same theme.
Keywords: Exile; reminiscences; space; escape; influence; melhoun; Moroccan folk literature